PENGEMBANGAN APLIKASI BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN ILMU TAJWID DI TPQ HIDAYATUL MUTTAQIN - rouf, muhamad abdul (Joined Journal (Journal of Informatics Education), 2019)
ABSTRACT Based on the implementation and the results of tests that have been carried out it can be concluded that this application runs well in accordance with its function. This application runs on Android-based smartphones which are basically learning applications and have been able to teach terms related to the problem of recitation. add interest and knowledge in the material of tajweed especially in the mention of stand-alone hijaiyyah letters and when meeting with other letters. And the most important thing can be a learning tool in reading the Qur'an in accordance with the Tajweed Sciences. The level of feasibility of the application of Android-based Tajweed is tested by media experts with a percentage of feasibility of 75% and material experts with a percentage of 87% feasibility and testing of learning media users with a feasibility rate of 89% and conclusively categorized as very feasible as a learning aid . This learning application is expected to be one of the alternatives in the Tajwid Science learning method and how to read the Qur'an properly and correctly. But for maximum results, learning recitation must be accompanied or guided directly by the teacher. Keywords: Keywords: Learning media, Android, Tajwid science.